'There are worse places than Dalmuir!' Glaswegian Riveters on the Clyde and the Copperbelt. Issue 3 (December 2015) - Money, Duncan
Abstract : This article follows the fortunes of a group of riveters who moved, briefly, from the Clyde to the Copperbelt to work on construction at the newly opened copper mines in the region in 1930. Escaping from Depression-era Glasgow, these volatile riveters clashed with hard-bitten American mine managers over wages, self-respect and the colour bar in southern Africa, events best understood within a framework of the transnational world of white labour. The history of labour migration in colonial Africa has been studied almost exclusively in terms of African labour yet large numbers of people arrived from outside the continent to work on the mines in central and southern Africa. Although only a sliver of these wider population flows, the riveters provide a snapshot in the wider British labour movement and movements of white migrants during this period. This article argues that their experiences illustrate the curious, influential politics of 'white labourism' where political radicalism and industrial militancy were intricately linked to white domination and racial segregation. Drawing on records from the mining companies, it will be demonstrated that these men saw themselves as militant representatives of an international working class, but one strictly delineated on racial lines.